2021
DOI: 10.1080/14766825.2021.1876717
|View full text |Cite
|
Sign up to set email alerts
|

Plant-based diets and destination image: a holistic approach

Abstract: A growing number of individuals in contemporary society follow a plant-based diet due to discourse and debates around the environmental impacts, the treatment of animals and healthrelated issues associated with animal agriculture. At the same time, food is regarded as a gateway to experience authentic elements of local cultures, traditions and heritage. This raises questions about the influence that plant-based diets that strictly exclude all forms of produce derived from animals exerts on the tourist's destin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…Differences were found among demographic groups and their consumption patterns in relation to motivations, food attractiveness and satisfaction/loyalty. These findings are consistent with Guachalla (2021) by indicating that various people have dissimilar perceptions and satisfaction with plantbased diets due to levels of familiarity with the health considerations related to plantbased foods.…”
Section: Discussion and Theoretical Implicationssupporting
confidence: 88%
See 1 more Smart Citation
“…Differences were found among demographic groups and their consumption patterns in relation to motivations, food attractiveness and satisfaction/loyalty. These findings are consistent with Guachalla (2021) by indicating that various people have dissimilar perceptions and satisfaction with plantbased diets due to levels of familiarity with the health considerations related to plantbased foods.…”
Section: Discussion and Theoretical Implicationssupporting
confidence: 88%
“…Does a healthy diet travel? This research provides evidence that the answer to this question is in the positive; there are indeed people who seek out these specialized restaurants and plant-based diet menu offerings at their destinations (Guachalla, 2021).…”
Section: Discussion Implications and Conclusionmentioning
confidence: 94%
“…At a practical level, the authors concluded that plant-based restaurant operators and managers should have a deeper understanding of the distinctive characteristics of their target market. Guachalla (2021) looked to understand how people following a plant-based diet for environmental, ethical, and health reasons influenced tourists' destination images from cognitive, affective and conative dimensions. The findings suggested strict plant-based diets stimulated "destination images of social belonging, images off-the-beaten-track, images of cosmopolitanism, and images of emotional solidarity rooted in these tourists' personal normative belief".…”
Section: Cameo Literature Reviewmentioning
confidence: 99%
“…This shared faith and value makes people feel they belong to a community (Shin et al , 2021), that is, the Muslim community. This feeling of belongingness shapes a person's cohesion with the community, subsequently impacting their behaviour towards the community (Guachalla, 2022; Söderlund, 2019). Further, past empirical studies hint at the positive impact of a sense of community on purchasing a product and a service associated with the community (Cappelli et al , 2022; Ferguson and Thompson, 2021; Peterson et al , 2008).…”
Section: Introductionmentioning
confidence: 99%